African and Africa-Related Nobel Prize Winners Portraitures in excellence - Afulezi, Uju Nkwocha (Boston University Press of America, 2002)
In African and Africa-Related Nobel Prize Winners, Uju Nkwocha Afulezi and Ugochukwu Uju Afulezi present the first assembled information on African and Africa-related Nobel Prize winners. The information presented reveals what made these individuals special and worthy of the prize. Through this presentation, the editors help to highlight the relationship between Nobel Prizes and the Black or African contributions at the highest level of human engagements.
Keywords: Nobel Prizes-History